Spatial correlation robust inference with errors in location or distance - Timothy G. Conley; Francesca Molinary (Centre for Microdata Methods and Practice (cemmap), 2005)
This paper presents results from a Monte Carlo study concerning inference with spatially dependent data. It investigates the impact of location/distance measurement errors upon the accuracy of parametric and nonparametric estimators of asymptotic variances.
Keywords: 330